Implementasi Kahoot dalam Pembelajaran Bahasa Prancis pada Masa Pandemi Covid-19 di SMK DKI Jakarta - Asti Purbarini; Sri Harini Ekowati; Wahyu Tri Widyastuti (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
The information technology in learning during this pandemic situation is very important, because we did online courses, while not all teachers, including French teachers, are ready to do online courses. In learning stage there are preliminary, core and closing stages. In the preliminary stage contains information about Core Competencies (KI) and Basic Competencies (KD) that will be discussed, motivating students, apperception, etc. The core activity stage is the stage of making students understand the material in various ways and various media. The closing stage is to provide an evaluation, exercise, or test. This research focuses on the closing stage, which using Kahoot in the evaluation stage. Because not all French teachers know about Kahoot, this Kahoot implementation training becomes needed. The results are Kahoot documents made by French vocational schoolteachers. Kahoot is made according to their needs. There are 8 Kahoot documents with various KI and KD.